Impact of Surgical Technique on Long-term Complication Rate After Laparoscopic Adjustable Gastric Banding (LAGB): Results of a Single-blinded Randomized Controlled trial (ANOSEAN Study). Issue 5 (November 2016) - Le Coq, Benjamin; Frering, Vincent; Ghunaim, Mohammed; Campan, Pierre; Dabrowski, André; Mulliez, Emmanuel; Loridan, Eric; , Frédéric Combemale; Denimal, Franck; Torres, Fanelly; Baud, Gregory; Thibault, Camille; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of the study was to explore the impact of the absence of band fixation on the reoperation rate and to identify other risk factors for long-term complications. Background: Laparoscopic adjustable gastric banding has been demonstrated to permit important weight loss and comorbidity improvement, but some bands will have to be removed mainly for failure or in case of planned 2-step surgery. Then, the absence of a gastro-gastric suture (GGS) would allow easier band removal. There are insufficient data to conclude that GGS should be abandoned, as the associated risk of band slippage has not been prospectively assessed. Methods: The ANOSEAN study was a randomized controlled single-blind trial (CPP 2009-A00346–51). Primary outcome was reintervention rate for band removal or repositioning at 3 years. It included 706 patients in 17 bariatric centers. Patients in group 1 received a gastric band with GGS. Inclusion criteria were adapted from National Institutes of Health recommendations. Surgical technique was standardized among all surgeons. Results: At 3 years, the reintervention rate for band retrieval or repositioning was significantly higher in the absence of band fixation (19.4% vs11.3%; P = 0.013), partly because of the slippage rate (10.3% vs 3.6%; P = 0.005). Body mass index <40 kg/m 2 at baseline was also an independent risk factor of slippage (odds ratio 2.769, 95% confidence interval 1.373, 5.581). Conclusions: GGS prevents band slippage and lower reintervention rate at 3 years. Fixation could be discussed for patients with high BMI who are scheduled to undergo 2-step surgery, but it needs to be specifically assessed.